The Correlation between Sports Extracurricular and Social Behaviour of Students in Junior High School 1, Jekulo, Kudus - Giffari, Andre Giffari; Irawan, Fajar Awang (Sports Medicine Curiosity Journal, 2023)
This study aims to analyse the level of categories of students' social behaviour and the relationship between extracurricular activities and students' social behaviour. This study is an experimental quantitative study employing a pre-experimental design. The sample in this study was 156 students in grades VII-IX of junior high school. Data collection was carried out through a social behaviour test questionnaire sheet. The data was processed using the Correlation Test. The results indicate that (1) The highest level of student social behaviour is in the mediocre category at 55%, while the high category is 31%, and 14% is in the low category, (2) there is a strong correlation between extracurricular activities and students' social behaviour, with a coefficient of 0.848. The correlation coefficient demonstrates the close association between sport extracurricular activities and the social behaviour of students. This study concludes that the introduction of sports extracurricular activities substantially impacts students' social conduct. This is because all forms of extracurricular activities are cooperative training, which includes peer interaction, training activities, organizational activities, preparation for events, and participation in competitions or competitions that influence the development of positive character traits in students. It is intended that this research will have consequences for enhancing the development of extracurricular activities in schools so that they not only influence the pleasant social conduct of students but also produce exceptional seeds, which are the hope for Indonesia's future accomplishments.